Sports media in Algeria... From a profession of hardship to a profession of reward: A study of the level of professional pressures in media institutions - Salami, As'adani; belbar, Said (sports creativity, 2025)
This study attempts to identify the extent of professional pressures experienced by media professionals in Algeria, through a field survey of a sample of employees from various official and private media outlets across the country. Undoubtedly, the experience of Algerian sports media has spanned a significant period, necessitating in-depth studies of the personalities of media professionals in the country and, consequently, an evaluation of their working conditions and the media environment. This study seeks to investigate the concept of professional and psychological pressure, which is common in many professions that involve dealing with the general public. The media, by its very nature, is an open arena where media professionals strive to satisfy the public as much as possible, within the framework of societal norms and general rules.